Institutional Stagnation and Organizational Readiness in Establishing Higher Education: A Strategic Analysis of PCNU Bandung - Mifta Ghina Dzakiya; Neng Zahra Nafisa; Khoerunnisa Khoerunnisa; Irfan Ahmad Zain (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the readiness of organizational resources of PCNU Bandung City in the plan to establish a higher education institution and to map the challenges of institutional stagnation amidst modernity and the competitive urban higher education environment. This research employed a qualitative approach using a field research design. Data were collected through semi-structured interviews, participatory observation, and documentation involving twelve key informants representing the Syuriyah council, Tanfidziyah executive board, and the Nahdlatul Ulama Higher Education Institution (LPTNU) of PCNU Bandung City. Data validity was ensured through source triangulation, member checking, and prolonged engagement in the field. Data analysis followed the Miles, Huberman, and Saldana model, consisting of data condensation, data display, and conclusion drawing. The findings reveal that the absence of a physical higher education institution directly managed by PCNU Bandung City does not indicate complete institutional stagnation. Instead, it represents an internal consolidation strategy adopted by the organization. PCNU Bandung City prioritizes strengthening human resource capacity through the PD-PKPNU cadre development program, academic resource mapping, and the maturation of institutional design before accelerating physical infrastructure development. The SWOT analysis indicates that the organization’s primary strengths lie in its strong mass base and the authority of ulama figures, while its weaknesses relate to financial independence and uneven managerial capacity. Therefore, the current incubation phase is interpreted as a defensive-rational strategy to transform socio-cultural capital into professional institutional capacity in order to face the intense competition of higher education in urban settings